EFEKTIVITAS PENGGUNAAN TERMINAL BANDAR LAKSAMANA INDRAGIRI DI KOTA TEMBILAHAN - ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Development terminal inaugurated since year 2010 until today still minimum utilization and difficulty arrange to owners of public transport services to invited to operate in terminal similarly with public transport users. The aim of this research is to know effectiveness of the use of the terminal bandar laksamana indragiri at tembilahan city and other factors that influence effectiveness of the use of the terminal bandar laksamana indragiri at tembilahan cityThe concept theory that used is the concept effectiveness of Krishnomo (1998). This research is a qualitative in showed by using descriptive data. In this research, the wrier used interview techniques, observation, and documentation. By used of key informan as a source of informationThe result showed that the know effectiveness of the use of the terminal bandar laksamana indragiri at tembilahan city ineffective this is because level of service terminal not yet qualify standards of the passenger terminal, low service levels, as well as facilities provided for ease in reaching terminal (accessibility) which is not yet available. Ineffectiveness implies that terminal bandar laksamana indragiri at tembilahan city has not been able to provide satisfactory service for service users public transport drivers. Weak law enforcement in terminal operation settings to society and owners of public transport services are factors that affects effectiveness of the use of the terminal bandar laksamana indragiri at tembilahan city.Keywords : effectiveness, effectiveness criteria, Terminal Bandar Laksamana Indragiri